2011
DOI: 10.1002/mrm.24127
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer MRI in pancreatic cancer xenograft models

Abstract: Magnetization transfer (MT) MRI measurements were performed in 3 pancreatic ductal adenocarcinoma (PDAC) mouse xenograft models. For each of 28 PDAC xenografts, magnetization transfer ratios (MTR) were calculated and compared to histologic fibrosis levels from reference standard trichrome staining. MTR was found to be significantly higher in tumors grown using BxPC-3 cell line (39.4 ± 5.1, mean ± SD) compared to the MTR for the tumors grown from Panc-1 (32.4 ± 2.8) and Capan-1 (27.3 ± 2.9) cell lines (P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…Tumor perfusion can be characterized noninvasively by MRI, via application of DCE-MRI (34)(35)(36)(37). The DCE data indicating higher permeability supports the histologic analysis of perfusion and the IFP data: 3 days following Cellax treatment, the tumor vessel permeability in the core of tumors (K trans ) was significantly increased compared with other therapies (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Tumor perfusion can be characterized noninvasively by MRI, via application of DCE-MRI (34)(35)(36)(37). The DCE data indicating higher permeability supports the histologic analysis of perfusion and the IFP data: 3 days following Cellax treatment, the tumor vessel permeability in the core of tumors (K trans ) was significantly increased compared with other therapies (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The initially higher MT values at day 1 are probably due to the high collagen content used for injection of the hMPCs. This is supported by previous work on monitoring of intestinal fibrosis of Crohn disease (27), as well as a study on pancreatic cancer xenografts (28), which demonstrated a correlation of collagen content and high MTR values. The decrease of MT values from day 1 to day 3 is likely due to initial remodeling and degradation of the injected collagen, and only after day 3 do changes in MT values reflect the process of muscle fiber formation from injected hMPCs.…”
Section: Injected Hmpcs Form Functional Muscle Tissuesupporting
confidence: 78%
“…23 No significant difference in the longitudinal assessment of magnetization transfer ratio (MTR) signal between vehicle versus monotherapy or the combination treatment in PKT mice was seen despite a slower rate of tumor growth (Figure 5 D , E and F ). Contrary to our expectations, treatment with AZD1480 and gemcitabine did not deplete collagen or hyaluronan content despite the decrease in tumor size, decreased expression of the stromal effector SPARC and enhanced drug delivery to the tumor.…”
Section: Resultsmentioning
confidence: 97%